OSTRACODOS DE LA FORMACION CARMEN SILVA, MIEMBRO SUPERIOR (MIOCENO INFERIOR), ISLA GRANDE DE TIERRA DEL FUEGO, ARGENTINA. PARTE II. (Ameghiniana, 2013)
The study of ostracodes from one sample of the Upper Member of Carmen Silva Formation is finished in this article. Eigth species representing 6 genera are described. Six of them are proposed: Aurila bertelsae nov. sp., Cornucoquimba carmensilvaensis nov. sp., Patag onacythere australis nov. sp. P. sansebastianensis nov. sp. Cythecromorpha? fueguina nov. sp., Munseyella fuegoensis nov. sp. Two taxa have not been named because the scarse material. Two species are doubtfully placed in their respective genera. The ostracodes are generally well preserved but they are poor in number of specimens. Most caparaces are ornamented, moderately to strongly calcified and medium in length. The species seem to be closely related with ostracodes from the Cenozoic of Santa Cruz, Buenos Aires and Santa Fe provinces (Argentina), Chile, Brazil, Antarctica and Australia. The ostracodes appear to have lived in a shallow sea.